Ceramic tubular MOF hybrid membrane fabricated through in situ layer‐by‐layer self‐assembly for nanofiltration. Issue 2 (8th December 2015) - Wang, Naixin; Liu, Tianjiao; Shen, Hongpan; Ji, Shulan; Li, Jian‐Rong; Zhang, Rong
Abstract : Nanofiltration has been playing an important role in water purification, in which the developments of novel membrane materials and modules are among significant. Herein, a metal‐organic framework (MOFs) hybrid membrane, ZIF‐8/PSS was fabricated on a tubular alumina substrate through a layer‐by‐layer self‐assembly technique. ZIF‐8 particles in situ grow into PSS layers to improve their compatibility and dispersion, thereby getting high quality membrane, which was loaded into a steel tubular module for nano‐filtrating dyes from water. Under optimized conditions, it shows outstanding nanofiltration properties toward methyl blue, with the flux of 210 Lm −2 h −1 MPa −1 and the rejection of 98.6%. Furthermore, the good pressure resistance ability and running stability of the membrane were revealed, which can be attributed to use the ceramic substrate and the inherent stability of ZIF‐8. This work thus illustrates a simple approach for fabricating MOFs hybrid membranes on tubular ceramic substrates, having great potential for industrial applications. © 2015 American Institute of Chemical Engineers AIChE J, 62: 538–546, 2016